1991
DOI: 10.1007/bf00194056
|View full text |Cite
|
Sign up to set email alerts
|

Oriented movement of statoliths studied in a reduced gravitational field during parabolic flights of rockets

Abstract: During five rocket flights (TEXUS 18, 19, 21, 23 and 25), experiments were performed to investigate the behaviour of statoliths in rhizoids of the green alga Charo globularia Thuill. and in statocytes of cress (Lepidium sativum L.) roots, when the gravitational field changed to approx. l0(-4) g (i.e. microgravity) during the parabolic flight (lasting for 301-390 s) of the rockets. The position of statoliths was only slightly influenced by the conditions during launch, e.g. vibration, acceleration and rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 26 publications
(31 reference statements)
3
38
0
2
Order By: Relevance
“…The number of statoliths (50-60 per cell) observed in SW rhizoids is similar to values previously reported in the literature for mature Chara rhizoids (generated from thallus cuttings) grown in either Foresburg medium (which is a more enriched medium than APW) or agar without any nutrients (Sievers, 1971;Sievers and Volkmann, 1979;Hejnowicz and Sievers, 1981;Bartnik and Sievers, 1988;Volkmann et al ;1991;Braun and Sievers, 1993). However, several studies have demonstrated that immature, developing Chara rhizoids contain fewer statoliths than do mature rhizoids (Schroter et al, 1973;Kiss, 1992).…”
Section: Discussionsupporting
confidence: 85%
“…The number of statoliths (50-60 per cell) observed in SW rhizoids is similar to values previously reported in the literature for mature Chara rhizoids (generated from thallus cuttings) grown in either Foresburg medium (which is a more enriched medium than APW) or agar without any nutrients (Sievers, 1971;Sievers and Volkmann, 1979;Hejnowicz and Sievers, 1981;Bartnik and Sievers, 1988;Volkmann et al ;1991;Braun and Sievers, 1993). However, several studies have demonstrated that immature, developing Chara rhizoids contain fewer statoliths than do mature rhizoids (Schroter et al, 1973;Kiss, 1992).…”
Section: Discussionsupporting
confidence: 85%
“…There are several reports indicating that the actomyosin system is involved in the positioning of statoliths and in the modulation of the sedimentation process in order to meet specific requirements for a most beneficial gravitropic response (Sievers et al, 1991a;Volkmann et al, 1991Volkmann et al, , 1999Driss-Ecole et al, 2000;Perbal et al, 2004). Although the kinetics of statolith movements have been analyzed in gravisensing cells of shoots (Sack et al, 1984;Saito et al, 2005) and roots (Sack et al, 1985(Sack et al, , 1986MacCleery and Kiss, 1999;Yoder et al, 2001), interpretation of the results with respect to gravity sensing is difficult because the interaction between statoliths and the cytoskeleton and its role in the graviperception mechanism is far from being understood in these cell types.…”
Section: Gravisensitivity Is Determined By Molecular Interactions Betmentioning
confidence: 99%
“…Any deviation from the vertical growth direction, however, causes statoliths to sediment onto a specific gravisensitive area of the subapical cell flank, thereby initiating the gravitropic curvature response. Abolishing the gravity force results in an axial displacement of statoliths away from the cell tip (Volkmann et al 1991;Buchen et al 1993;Braun et al 2002). Data on the dynamics of this movement of statoliths is available from various real μg conditions like parabolic plane flights, sounding rocket missions (TEXUS, MAXUS) and several space shuttle missions (Bunchen et al 1991(Bunchen et al , 1993Volkmann et al 1991;Braun et al 2002;Limbach et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Abolishing the gravity force results in an axial displacement of statoliths away from the cell tip (Volkmann et al 1991;Buchen et al 1993;Braun et al 2002). Data on the dynamics of this movement of statoliths is available from various real μg conditions like parabolic plane flights, sounding rocket missions (TEXUS, MAXUS) and several space shuttle missions (Bunchen et al 1991(Bunchen et al , 1993Volkmann et al 1991;Braun et al 2002;Limbach et al 2005). Chara rhizoids which have already been studied on 2D-and 3D clinostats (Cai et al 1997;Hoson et al 1997;Braun et al 2002) showed similar effects like in real microgravity.…”
Section: Introductionmentioning
confidence: 99%